N‐Heterocyclic Carbene Catalysis via Azolium Dienolates: An Efficient Strategy for Remote Enantioselective Functionalizations - Chen, Xiang‐Yu; Liu, Qiang; Chauhan, Pankaj; Enders, Dieter (Angewandte Chemie International Edition, 2018)
N‐heterocyclic carbene (NHC) catalysis has emerged as a powerful strategy in organic synthesis. In recent years a number of reviews have been published on NHC‐catalyzed transformations involving Breslow intermediates, acyl azoliums, α,β‐unsaturated acyl azoliums, homoenolate equivalents, and azolium enolates. However, the azolium dienolate intermediates generated by NHCs have been employed in asymmetric synthesis only very recently, especially in cycloadditions dealing with remote functionalization. This Minireview highlights all the developments and the new advances in NHC‐catalyzed asymmetric cycloaddition reactions involving azolium dienolate intermediates. An intermediate look: N‐heterocyclic carbene catalysis has emerged as a powerful strategy for enantioselective functionalizations at remote positions, and proceeds via azolium dienolate intermediates that are easily generated from various substrates. This Minireview highlights the development and the new advances of cycloaddition/annulation reactions involving azolium dienolate intermediates.